Men and Masculinities in Contemporary China. - Song, Geng (Women and gender in China studies., 2013)
In Edited byMen and Masculinities in Contemporary ChinaEdited by, Geng Song and Derek Hird offer an account of Chinese masculinities in media discourse and everyday life, covering masculinities on television, in lifestyle magazines, in cyberspace, at work, at leisure, and at home.